Thermal Activation of Regenerated Grating in Hydrogenated Gallosilicate Fiber - Gunawardena, D.S.; Mat-Sharif, K.A.; Lai, M.H.; Lim, Kok Sing; Tamchek, N.; Omar, N.Y.M.; Emami, S.D.; Muhamad-Yasin, S.Z.; Zulkifli, M.I.; Yusoff, Z.; Yang, H.Z.; Abdul-Rashid, H.A.; et al. (Institute of Electrical and Electronics Engineers (IEEE), 2016)
The thermal regeneration of fiber Bragg gratings inscribed on hydrogenated gallosilicate optical fiber, fabricated using a modified chemical vapor deposition (MCVD) technique followed by a solution doping process, is demonstrated for the first time. A type-I seed grating is thermally regenerated and the evolution of the grating reflectivity in a temperature range between 25 °C and 720 °C is investigated. Temperature responses of 15.2 pm/°C and 15.0 pm/°C are obtained during heating and cooling processes of the regenerated grating (RG), respectively, when performing thermal calibration over a temperature range of 25 °C-750 °C and vice versa. Gallosilicate-based RGs are potential candidates as high-temperature resistant gratings in rare-earth-doped fiber, since they provide high photosensitivity and thermal sustainability with the involvement of a single dopant with a concentration as low as 5 wt%.